SUBSTANTIATION OF SYSTEM COMPONENTS MORAL EDUCATION OF THE FUTURE BORDER OFFICERS - Gryaznov І.О. (Pedagogy of Higher and Secondary Education, 2004)
In the article, the author discredits the purposes, components, objects, content of moral bringing up of future officers.